Study of the properties of gray cast iron with added niobium for hot work (Research, Society and Development, 2021)
One of the main materials used in the production of automobile parts is gray cast iron. This material is widely used in the production of brake discs. The aim of this study was to evaluate the mechanical and physical behavior of four pearlitic gray cast iron alloys. For this purpose, four alloys named: base alloy, base alloy + 0.10% Nb, base alloy + 0.20% Nb and base alloy + 0.15% Mo, were cast and subsequently evaluated for: chemical composition, tensile strength at temperatures of 22°C, 380°C, 480°C, 580°C and 680°C, hardness, microstructure and thermal diffusivity. In tensile strength tests at temperatures from 22°C to 680°C, it was observed that when added to the base alloy, the elements niobium and molybdenum increase the strength limit of gray cast iron, as they form carbides and promote the refining of perlite. The addition of Nb or Mo also increased the hardness of the alloys in relation to the base alloy. Regarding the microstructure, it was also possible to observe that the alloys with the addition of Nb or Mo had slightly more refined graphite. Diffusivity tests showed that the base cast iron + 0.10% Nb has better diffusivity results at all tested temperatures (380°C, 480°C, 580°C, and 680°C). This fact may be associated with the increased amount of graphite and the addition of 0.10% niobium content.